Elimination of biofilm and microbial contamination reservoirs in hospital washbasin U-bends by automated cleaning and disinfection with electrochemically activated solutions. Issue 2 (October 2016) - Swan, J.S.; Deasy, E.C.; Boyle, M.A.; Russell, R.J.; O'Donnell, M.J.; Coleman, D.C.
Summary: Background: Washbasin U-bends are reservoirs of microbial contamination in healthcare environments. U-Bends are constantly full of water and harbour microbial biofilm. Aim: To develop an effective automated cleaning and disinfection system for U-bends using two solutions generated by electrochemical activation of brine including the disinfectant anolyte (predominantly hypochlorous acid) and catholyte (predominantly sodium hydroxide) with detergent properties. Methods: Initially three washbasin U-bends were manually filled with catholyte followed by anolyte for 5 min each once weekly for five weeks. A programmable system was then developed with one washbasin that automated this process. This U-bend had three cycles of 5 min catholyte followed by 5 min anolyte treatment per week for three months. Quantitative bacterial counts from treated and control U-bends were determined on blood agar (CBA), R2A, PAS, and PA agars following automated treatment and on CBA and R2A following manual treatment. Findings: The average bacterial density from untreated U-bends throughout the study was >1×10 5 cfu/swab on all media with Pseudomonas aeruginosa accounting for ∼50% of counts. Manual U-bend electrochemically activated (ECA) solution treatment reduced counts significantly (<100 cfu/swab) ( P  < 0.01 for CBA; P  < 0.005 for R2A). Similarly, counts from the automated ECA-treatment U-bend were significantly reduced with average counts for 35 cycles on CBA, R2A, PAS, and PA of 2.1 ± 4.5 ( P  < 0.0001), 13.1 ± 30.1 ( P  < 0.05), 0.7 ± 2.8 ( P  < 0.001), and 0 ( P  < 0.05) cfu/swab, respectively. P. aeruginosa was eliminated from all treated U-bends. Conclusion: Automated ECA treatment of washbasin U-bends consistently minimizes microbial contamination.